New Mining Tools and Methods for Roadheader Mining Heads - Kotwica, Krzysztof; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book introduces new solutions for mining tools, unique lubricated holders and mining methods for hard-rock mining using mini-disk tools. In the first part, it describes problems connected with hard-rock mining using traditional mining methods like cutting. Then an alternative for conical pick is discussed, the so-called crown or bell pick and a new solution of a holder for conical picks allowing for tool rotation. These solutions should make it possible to increase the durability of cutting tools. The final part of the book explains a new mining head solution with mini-disk tools and a complex motion trajectory. With this, mining heads can be replaced in currently used roadheaders instead of standard mining heads. This book can be used by employees of the mining industry, manufacturers of mining tools, machines and equipment, as well as employees and students of mining and mechanical faculties of technical universities.
Chapter 1. Introduction -- Chapter 2. Problems of hard rock mining using cutting tools -- Chapter 3. The hard rock mining using disk tools -- Chapter 4. The crown pick as an alternative for the conical pick -- Chapter 5. Lubricated holder for conical pick -- Chapter 6. The mining head with mini-disk tools with complex motion Trajectory -- Chapter 7. Summary and final comments.
Keywords: Underground construction; Mining engineering; Manufactures; Geotechnical engineering; Underground Engineering and Tunnel Construction; Mining and Exploration; Machines, Tools, Processes; Geotechnical Engineering and Applied Earth Sciences; Mining machinery -- Parts; Rock splitters (Machines)